2014
DOI: 10.1021/jz502111u
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis Analysis Based on the Ferroelectric Effect in Hybrid Perovskite Solar Cells

Abstract: The power conversion efficiency (PCE) of CH3NH3PbX3 (X = I, Br, Cl) perovskite solar cells has been developed rapidly from 6.5 to 18% within 3 years. However, the anomalous hysteresis found in I-V measurements can cause an inaccurate estimation of the efficiency. We attribute the phenomena to the ferroelectric effect and build a model based on the ferroelectric diode to explain it. The ferroelectric effect of CH3NH3PbI3-xClx is strongly suggested by characterization methods and the E-P (electrical field-polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
355
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(371 citation statements)
references
References 28 publications
15
355
0
1
Order By: Relevance
“…[189] Li et al [115] also mentioned the often-observed kinks illustrated in Figure 6 in the J-V curve measurement. Several groups have observed a similar behavior, [15,117,128,190,191] and this phenomenon especially prevails when using fast scan rates. In the context of the ion-migration model, the authors found an explanation for this kink in the J-V curve.…”
Section: Modulation Of the Energetic Environment At Interfacesmentioning
confidence: 67%
“…[189] Li et al [115] also mentioned the often-observed kinks illustrated in Figure 6 in the J-V curve measurement. Several groups have observed a similar behavior, [15,117,128,190,191] and this phenomenon especially prevails when using fast scan rates. In the context of the ion-migration model, the authors found an explanation for this kink in the J-V curve.…”
Section: Modulation Of the Energetic Environment At Interfacesmentioning
confidence: 67%
“…In spite of the spectacular advances in cell efficiency many important aspects of the experimental observations on this system are not understood. Particularly intriguing is the hysteresis features in the response of the current density-voltage ( V J − ) curves [10][11][12][13] that have been related to a number of different explanations, as ferroelectric properties of the perovskite materials, [14][15][16] delayed electronic trapping processes, [17] or slow ion migration. [11,18,19] The recognition that the solar cell performance is heavily affected by time scale of the measurement and preconditioning procedures [9,17,20,21] has raised many concerns about the stability of the device and reliability for long time operation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Also, in photovoltaics, perovskitebased solar cells constitute a special type of light-harvesting devices because, in addition to electronic mechanisms, the presence of moving ionic species is believed to modify current-voltage curves. 3,4 Among other explanations related to either ferroelectricity [5][6][7] or electronic trapping properties of perovskites, 8 there is growing consensus that the ionic kinetics lies behind the commonly observed current-voltage hysteretic response, [9][10][11] and switchable photovoltaic characteristics. 12 Several studies have analyzed the defect chemistry of hybrid perovskite materials, and the inherent dependence of their doping character on the processing route.…”
mentioning
confidence: 99%